Betulinic acid inhibits cell proliferation and fibronectin accumulation in rat glomerular mesangial cells cultured under high glucose condition - Liu, Chun-mei; Qi, Xue-lin; Yang, Ya-feng; Zhang, Xiu-de (Biomedicine & pharmacotherapy, 2016)
[Display omitted] Glomerular mesangial cells (MCs) proliferation and extracellular matrix (ECM) accumulation have been recognized as major pathogenic events in the progression of diabetic nephropathy. Betulinic acid (BA), (3β-hydroxy-lup-20(29)-en-28-oic acid), is a naturally occurring pentacyclic lupane group triterpenoid, and it has been shown to possess glucose-lowering property. However, the role of BA on MC proliferation and ECM accumulation in diabetic condition remains unclear. So, in the present study, we investigated the role of BA on cell proliferation and ECM accumulation in rat glomerular MCs cultured under high glucose (HG) condition. In the current study, we demonstrated that BA suppressed HG-induced MC proliferation, arrested HG-induced cell-cycle progression, reversed HG-inhibited expression of p21Waf1/Cip1 and p27Kip1. It also suppressed HG-induced fibronectin (FN) expression in MCs. Furthermore, BA inhibited HG-induced phosphorylation of ERK1/2 and p38MAPK in MCs. In conclusion, our present study demonstrated that BA inhibited HG-induced cell proliferation and FN expression in MCs via inhibiting ERK1/2 and p38MAPK pathways. Thus, BA may serve as a potential drug for the treatment of diabetic nephropathy.